Penatalaksanaan Penyakit Paru Obstruktif Kronik (PPOK) dengan Hipertensi Melalui Pendekatan Kedokteran Keluarga Lisa Ayu Pratiwi1, TA Larasati2 - Lisa Ayu Pratiwi; T.A. Larasati (CV. Jasa Sukses Abadi, 2020)
Chronic Obstructive Pulmonary Disease (COPD) is still a major problem in public health in the world and in Indonesia. In the development of the disease, COPD can be accompanied by hypertension either due to exposure to COPD risk factors or to go hand in hand as a comorbid disease. COPD and hypertension are problems so pay attention to the patient in the management of the disease. Application of Evidence Base Medicine based services to these patients to identify risk factors in the form of lifestyle and clinical problems as well as patient centered management and family approach. This study uses primary data directly from patients and secondary data obtained from patient medical records. The assessment in this case is based on a holistic diagnosis from the beginning, process, and end of the study in a qualitative and quantitative manner. 56-year-old patient with male sex comes with complaints, cough with phlegm Accompanied by shortness of breath lost arise, since 5 days ago. On physical examination obtained blood pressure 160 / 90mmhg breathing frequency 24 times per minute. In the thoracic region examination there is a Barrel Chest, widening of the rib cage, normal vesicular, positive rhonchi, negative wheezing. Internal factors in the form of age 56 years male gender lack of knowledge about COPD disease and hypertension, the purpose of treatment and the prognosis of the disease suffered. . External factors lack understanding about patient disease, lack of awareness of family members not to smoke in the house and cook with a stove. Then the patient and family intervene about the causes, risk factors, clinical symptoms, prognosis, and prevention of recurrence that can be done. So in the evaluation we found the patient had shown improvement with indicators using a questionnaire.